La imaginación en la tradición metafísico-mística: de Platón a Marsilio Ficino - Walerich, Alicja (Veritas, 2015)
The objective of the article is to examine the role of the image and imagination from the perspective of the tripartite mystical process based on the tradition of Pseudo-Dionysius the Areopagite. I distinguish in the first stage of this process the symbolical theology related to the external and sensuous experience; in the second stage the rational cognition and internal experience; in the last stage the mystical theology related to the supranatural experience. I arrive at a conclusion that in the first stage the imagination exceed the exterior and superficial character which was attributed traditionally to it, because various metaphysical and mystical authors introduce in the context of it a moment of a intuitive comprehension. In the second stage it is not only a basis of discursive thinking but it constitutes spiritual exercise which should intensify the process of thinking. In the third stage the image and imagination are a medium which help to overcome the ineffability of the mystical experience (English)